Everolimus and pancreatic neuroendocrine tumors (PNETs): Activity, resistance and how to overcome it. (September 2015) - Capozzi, Monica; Caterina, Ieranò; De Divitiis, Chiara; von Arx, Claudia; Maiolino, Piera; Tatangelo, Fabiana; Cavalcanti, Ernesta; Di Girolamo, Elena; Iaffaioli, Rosario Vincenzo; Scala, Stefania; Tafuto, Salvatore; ,
Abstract: Neuroendocrine tumors (NET) are rare malignancies, with the most common site of origin being from the gastrointestinal tract, particularly the pancreas, small bowel and appendix. Pancreatic neuroendocrine tumors (PNETs) can be functional, hormone secreting tumors, and can have distinctive symptoms leading to the diagnosis. In contrast nonfunctional tumors, the majority of PNETs, usually present later either incidentally or due to tumor bulk symptoms. Currently Everolimus, an inhibitor of mammalian target of rapamycin (mTOR), is the most promising drug for patients with unresectable, metastatic disease, in progressive well-differentiated PNETs and many studies are ongoing to demonstrate its effects on the other neuroendocrine histotipes. Food and Drug Administration (FDA) and European Medicines Agency (EMA) registered Everolimus in advanced/metastatic breast cancer, in advanced/metastatic renal cell carcinoma and in well/moderately differentiated pancreatic neuroendocrine tumors. Nevertheless only a subset of patients respond to the therapy due to the development of drug resistance. Thus the powerful Everolimus antitumor activity have prompted extensive efforts to overcome drug resistance and to maximize clinical benefit. In this review we aim to summarize current knowledge on mechanisms of Everolimus and other mTOR inhibitors molecules resistance with the intent to overcome it.